The zebra wall - Henkes Kevin 1960-; Kevin Henkes (New York : Scholastic, 1988)
When ten-year-old Adine's mother has a new baby, eccentric Aunt Irene comes to stay and shares Adine's bedroom--an event which requires a great deal of adjustment.
M
800